TERMITES. - Wan Nurainie, Wan Ismail; Ratnawati, Hazali; Norsyarizan, Jamil; Siti Shamimi, Abidin (UNIMAS Publisher, Sarawak Forestry Corporation, Natural History Publications (Borneo), Sarawak, 2022)
Termites are social insects with a well-developed caste system, their community acting as ecosystem engineers and decomposers. Termites are also environmental bioindicators in tropical rainforests, being responsive to biotic or abiotic change, and are thus suitable models to evaluate disturbance (Davies, 2002) and are potential indicators of climate change (Gathorne-Hardy, 2004)